Potential of Heritage Trails for Visitors Engagement: A Survey on Community Perceptions and Role of Technologies in the Case of Bandar Penggaram, Johor, Malaysia - Mat Radzuan, Indera Syahrul; Seow Ta Wee, Seow Ta Wee; Mohd Akmal Rohiat, Mohd Akmal Rohiat; Md Saman, Nor Hisham (Sage, 2025)
This study, centred on community perceptions, seeks to assess the feasibility of implementing heritage trail mapping in Bandar Penggaram, Batu Pahat, Johor, Malaysia. Its objective is to construct a comprehensive profile and delineate the cultural heritage features of Bandar Penggaram, emphasizing its distinctiveness within historical, economic, socio-cultural and environmental frameworks. Employing a mixed-method approach, the research administers questionnaire surveys and facilitates focus group discussions and interviews involving diverse public and private stakeholders. Findings reveal a prevailing belief among respondents that Bandar Penggaram’s heritage zone holds considerable potential to allure tourists and scholars alike. Moreover, the study underscores the imperative of incorporating emerging technologies and fostering stakeholder collaboration to augment community awareness regarding the historical significance of the port town’s heritage zone. Additionally, it delves into the historical importance of Bandar Penggaram, traces its economic ramifications in tourism, scrutinizes its sociocultural dynamics and addresses environmental sustainability concerns. Notably, the investigation uncovers a lack of utilization of cutting-edge technology in preservation efforts for Bandar Penggaram, potentially exposing heritage sites to irreversible harm. This article strives to underscore the critical importance of integrating technology into heritage site preservation, advocating for adopting advanced tools and methodologies. Furthermore, it proposes policy implications to nurture effective heritage conservation practices conducive to sustainable tourism development.